Hieracium lomniczkianum (Asteraceae), a new species in the H. wiesbaurianum aggregate from the Sudetes in Poland - Szeląg, Zbigniew (Phytotaxa, 2023)
Hieracium lomniczkianum is a new, apomictic species, discovered in the Karkonosze Mountains (Giant Mountains) in the Sudetes, SW Poland. It belongs to the H. wiesbaurianum aggregate which comprises taxa intermediate in characters between H. bifidum s.lat. and H. schmidtii s.lat. The new species is distinguished by a slender stem with small capitula, and by narrow, weakly dentate rosette leaves which are gradually tapered to a winged petiole.